Understanding the burden of HIV-related cancers in South Africa's Eastern Cape Province: A 2002-2017 retrospective study - Ncinitwa, Akhona (Department of Public Health and Family Medicine, 2026)
Background: The Human Immunodeficiency Virus (HIV)-related cancers in South Africa are a critical public health issue that echoes trends seen across other low-middle income countries (LMICs). These cancers include Kaposi sarcoma, non-Hodgkin's lymphoma, and cervical cancer. Understanding the HIV-related cancer trends and incidence is crucial for achieving improved health outcomes. Therefore, this study aims to understand the HIV- related cancers in the Eastern Cape province of South Africa Methods: This retrospective study used secondary analysis of data generated by the Eastern Cape Cancer Registry linked to the HIV database from the National Health Laboratory Services through probabilistic record linkage to identify and characterise cancer among people living with HIV. Included were cancer cases reported between 1st January 2002 and 31st December 2017 of adult men and women diagnosed with HIV-related cancers. Statistical analysis was done using STATA18.0. A join-point regression model was used to characterise the cancer trends. The Kaplan-Meier curve was used for survival analysis. Results: The sample comprised 1183 eligible cancer patient records, with 1044 (88.3%) females. The HIV prevalence among cancer patients was 74.5%. Specifically, 75.5% of males and 74.3% of females were living with HIV. The trends of Kaposi sarcoma showed an increase between 2002 and 2015 with an annual percentage change (APC) of 17.4%, and between 2015 and 2017, trends decreased with an APC of 22.6%. Cervical cancer trends decreased between 2002 and 2004 with an APC of 14.4%; from 2004 to 2017, there was a sharp increase of 33.2% APC. Kaposi sarcoma had the highest survival median of 3.1 years (p=0.06) for people living with HIV, followed by non-Hodgkin's lymphoma with 2.9 years (p=0.96), and lastly cervical cancer with 2.5 years (p=0.73). Conclusion: The growing burden of cervical cancer and Kaposi sarcoma among people living with HIV remains a problem in the Eastern Cape. Therefore, targeted interventions such as regular screening, early diagnosis, access to appropriate treatment, a system to track treatment adherence and survival rates, appropriate resource allocation, and targeted educational programmes are needed to address the burden.